Delimitation and Correlation of Civil and Administrative Legal Proceedings: Qualification Problems and Criteria (Lex localis - Journal of Local Self-Government, 2020)
This article is devoted to the problem of delimitation and correlation of civil and administrative manners of proceeding. The purpose of the research is to define clear criteria to delimit the civil and administrative legal proceedings to increase the efficiency of civil and administrative legislation regulations when solving disputes connected with the violation of rights, liberties and legitimate interests of an individual. The said is based on the hypothesis that the scope of public-administrative relations is wider than the scope of relations that are governed by the norms of administrative law. Classification problem in the study is considered in the context of defining proceeding manners (administrative or civil). Besides, the cases of courts of general jurisdiction have served as a research base. The author suggests some criteria models for delimiting administrative and civil court proceedings by the legal classification between the parties as well as by the suit character of stated claims. The latter in the future might lead to the formation of new, more accurate methods of applying administrative norms and a reduction in the number of precedents for incorrect proceedings.